Boy swallows universe : a novel - Dalton, Trent (New York, N.Y. : Harper, an imprint of HarperCollinsPublishers, 2019)
Exiled in a drug-oppressed refugee suburb in 1980s Australia, a twelve-year-old boy dreams of a career in journalism while fending off the local criminal element to protect his imprisoned mother.
Keywords: Boys -- Australia -- Fiction; Families -- Australia -- Fiction; Boys -- Australia -- Fiction; Family life -- Australia -- Fiction; Brisbane (Qld.) -- Fiction; Brisbane (Qld.) -- Fiction; Coming of age fiction